Littératies numériques : quels enjeux pour la didactique de l’écriture-lecture ? - Marie-Claude Penloup (Recherches en didactique des langues et des cultures)
The digital revolution has introduced new kinds of written genres as well as new forms related to writing that the learner has to master. It provides, at the same time, new tools for the teaching and learning of reading and writing. It is within this double framework that the questions of teaching written French using digital literacies are evaluated. The emphasis is on the changing attitudes that these new forms of literacy imply for teachers and the gains that could be attained in the school context from a global reconsideration of the teaching of French writing, whether it be electronic or not.